RAINFALL TREND ANALYSIS OF A MINI WATERSHED: A CASE STUDY ON DEGRADING LAKES/TANKS - K.P., Pradeep Raja; Reddy, Suresh Ramaswwamy (International Journal of Research -GRANTHAALAYAH, 2018)
India as a tropical country, depends solely on south west Monsoon. Southwest monsoon spans between June and September. The present study is aimed to carry out the probable trend of rainfall and to evaluate its implications on the tanks in Hunsur taluk of Mysore district, Karnataka, India. These tanks were the livelihood sources of water for the farmers in the command area. The lakes considered under this case study have been completely dried up in the recent past. Inconsistency of rainfall is one of the factors which govern the degradation of Lakes. Trend analysis is carried on 40 years daily rainfall data (1975-2014) for monthly, seasonal and annual average values using Mann-Kendall test and Sen’s slope estimation. The analysis shows ‘no trend’ for the months of January, February, March and June. There is an ‘increasing trend’ for the months of August, October and December. However, there is a ‘decreasing trend’ for the months of April, May, July, September and November. The decadal variation indicates a very significant decrease of rainfall for the months of June and July; particularly in the recent decade (2005-2014) and hence a ‘negative trend’ in the South-West monsoon. This may be one of the reasons for the deterioration of tanks in the study area.